2022
DOI: 10.1186/s12284-022-00573-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Agricultural Traits While Maintaining High Resistant Starch Content in Rice

Abstract: Background Resistant starch (RS) is beneficial for human health. Loss of starch branching enzyme IIb (BEIIb) increases the proportion of amylopectin long chains, which greatly elevates the RS content. Although high RS content cereals are desired, an increase in RS content is often accompanied by a decrease in seed weight. To further increase the RS content, genes encoding active-type starch synthase (SS) IIa, which elongates amylopectin branches, and high expression-type granule-bound SSI (GBSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Similar changes in amylopectin were observed in BEIIb CRISPR/Cas9 mutant of indica rice which has higher number of branches with DP 6, 7 and > 25 and lower number of chains with DP 9–24 leading to increased gelatinization temperature by 6 °C and increased amylose content by 7% 49 . Absence of BEIIb decreased the short chain number and increased the long chain number simultaneously 50 . In this study, SBEI expression was noted in all the varieties.…”
Section: Discussionmentioning
confidence: 94%
“…Similar changes in amylopectin were observed in BEIIb CRISPR/Cas9 mutant of indica rice which has higher number of branches with DP 6, 7 and > 25 and lower number of chains with DP 9–24 leading to increased gelatinization temperature by 6 °C and increased amylose content by 7% 49 . Absence of BEIIb decreased the short chain number and increased the long chain number simultaneously 50 . In this study, SBEI expression was noted in all the varieties.…”
Section: Discussionmentioning
confidence: 94%
“…The SSIIa and wx genotypes of rice lines used in this study are summarized in Table 1 . IR36 is known to possess the Wx a (or GBSS1 ) allele [ 3 ], whereas Akita 63 and Kinmaze, the parental line of EM204, are known to possess the Wx b (or gbss1 L ) genotype [ 3 , 39 ]; the Wx a and Wx b alleles can be distinguished from each other based on nucleotide polymorphisms in the first intron of the Wx gene [ 40 ]. These results show that rice lines generated in this study possess the expected genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…This might be because long amylopectin chains contribute towards more crystalline structure due to an increase in hydrogen bonds developed among the chains and thus increase the resistance to enzymatic hydrolysis (Sasaki et al 2009). A recent study has also shown that RS content in raw rice our is directly proportional to the content of amylose and long amylopectin chains (Miura et al 2022). It can be postulated that long amylopectin branches and amylose interact with each other during retrogradation to form imperfect helices, which prevents degradation by digestive enzymes and serves as RS2 and RS3.…”
Section: Starch and Its Component Variations Among The Rice Genotypesmentioning
confidence: 99%